Starlink’s Provision of Telecommunication Services During the Time of Armed Conflict and Its Consequences from the Perspective of Public International Law - Gerałt, Bartłomiej (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
This article attempts to provide an overview of the most important international regulations relating to the provision of telecommunication services by private companies to one or more belligerent parties in times of an armed conflict. Taking as an example the recently widely commented issue of Starlink allegedly withholding its services otherwise provided to the Ukrainian Armed Forces, this article reviews the issue from the perspective of general public international law as well as international space law. Specifically, the customs and regulations concerning the attributability of private parties actions as well as peaceful utilisation of outer space are scrutinised.